MORE ABOUT EPIDOTE AND CLINOZOISITE - White J.S. (My University, 2002)
Examines the chemical distinction between epidote and clinozoisite. Efficacy of optical mineralogy for chemical analysis; Contribution of Daniel E. Kile, geologists, on the definition of chemical composition of the minerals; Assessment on the color intensity of the minerals.
Keywords: EPIDOTE